Quelques figures de femmes dans les Belles Lettres frioulanes (xixe-xxe siècles) - Cristina Noacco (Revue des Langues Romanes)
From the mid-19th century to the present day, women’s literary creation in Friulian is quite rich and varied. We propose to retrace the main creations in Friulian of a few women of letters, highlighting the stylistic choices, the literary genres specifically selected and, above all, the psychological motivations which prompted these cultivated women to express themselves in Friulian, in preference to the official language of the country, Italian. Caterina Percoto celebrates the rural world, Maria Forte performs the work of an ethnologist when she records the expressions used by the characters in her stories, Novella Cantarutti describes a Friulian valley through the adoption of its dialectal variation, while Nelvia Di Monte recovers the language of her father as the repository of the culture of her family and her native land. These and other experiences which are described in this article are the fruit of an acute linguistic awareness and aim at increasing the value of Friulian as a literary language.